TRADISI TER-TERAN DALAM RANGKAIAN UPACARA TAWUR KESANGA MASYARAKAT DESA ADAT JASRI KARANGASEM - Ratna Dewi, Ni Luh Putu; Kebayantini, Ni Luh Nyoman; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Ter-Teran is a tradition practiced by people Village People Jasri located in the Village Subagan, Karangasem district, Karangasem regency. Ter-Teran tradition still maintained because it is a heritage that can strengthen the belief in religious teachings and to improve solidarity in society Jasri Village People, people believe the elimination of these traditions are believed to cause distress for the village. Ter-Teran tradition is maintained it contains positive meaning that are actualized in the social life of the Jasri traditional village. Keywords: ter-teran, religious rites, tawur kesanga, tradition, traditional village